PENDIDIKAN POLITIK BAGI MASYARAKAT PESISIR DI WILAYAH KECAMATAN BATU LAYAR KABUPATEN LOMBOK BARAT - Sally Salsabila; Saipul Hamdi; Anisa Pusparani; Dwi Setiawan Chaniago (Universitas Mataram, 2024)
Community service entitled Political Education for Coastal Communities in Batu Layar District, West Lombok Regency was carried out in Batu Layar District, West Lombok Regency. The urgency of this service is the relatively high number of abstainers in the 2019 Election in West Lombok Regency, which reached 26.44% or 9,670 people out of a total of 36,568 voters. This figure shows that there is still a need to increase political participation of the community in the General Election, including coastal communities in the Batu Layar District area. Political participation is not only important for the function of democracy, but also essential to ensure the legitimacy of the political system. Many previous studies have shown the important role of political socialization in helping individuals acquire values, attitudes, beliefs, which then have an impact on their political behavior in the existing political system, especially in the General Election. Therefore, this community service activity is important to be carried out so that public awareness in exercising their political rights in the 2024 Election can be further increased. The methods used in this activity are lectures and interactive dialogues by presenting Bawaslu and KPU commissioners of West Lombok Regency as resource persons.